2013
DOI: 10.1002/jat.2914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibitory effects between acetaminophen–glutathione conjugate and reduced glutathione in human glutathione reductase

Abstract: Acetaminophen overdose is the most frequent cause of acute liver injury. The main mechanism of acetaminophen toxicity has been attributed to oxidation of acetaminophen. The oxidation product is very reactive and reacts with glutathione generating acetaminophen-glutathione conjugate (APAP-SG). Although this conjugate has been recognized to be generally nontoxic, we have found recently that APAP-SG could produce a toxic effect. Therefore, the aim of our study was to estimate the toxicity of purified APAP-SG by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The increased hepatic GSH level could in part explain the hepatoprotective mechanism of tropisetron. Previous evidences showed that while the GSH content decreased below a threshold level, hepatic xanthine dehydrogenase can be converted to reversible xanthine oxidase, having an influence on superoxide radical generation and production [30, 31]. SOD is thought to be an important antioxidant enzyme, for it is closely related to the elimination of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…The increased hepatic GSH level could in part explain the hepatoprotective mechanism of tropisetron. Previous evidences showed that while the GSH content decreased below a threshold level, hepatic xanthine dehydrogenase can be converted to reversible xanthine oxidase, having an influence on superoxide radical generation and production [30, 31]. SOD is thought to be an important antioxidant enzyme, for it is closely related to the elimination of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced glutathione (GSH) is a tripeptide substance, including glutamate, cysteine, and glycine, which widely exists in normal cells in vivo . GSH can produce a variety of biochemical effects on cells, for example, it can be combined with a variety of chemical substances and their metabolites, and can remove the oxygen ions and other free radicals from the body . GSH, as the main metabolic regulation substance in human cells, can protect the cell membrane of liver cells, promote the activity of liver enzymes, and exhibit the detoxication and antioxidation effects .…”
Section: Introductionmentioning
confidence: 99%
“…8 GSH, as the main metabolic regulation substance in human cells, can protect the cell membrane of liver cells, promote the activity of liver enzymes, and exhibit the detoxication and antioxidation effects. 8 Currently, GSH has been used to treat CKD in clinical trials, mainly based on its role in scavenging oxygen free radicals. 9 In this study, we evaluated the effect of GSH on OS, angiogenesis factors and immune responses in diabetic CKD patients, providing new therapeutic targets for the treatment of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized PAC-quinone imine metabolites have also been shown to form GSH-conjugates which inhibit glutathione reductase (GR): the decreased activity of GR hampers the detoxification and antioxidant capacity of the GSH-GSSG cycle, further aggravating the pro-oxidative status in the cell (Nydlováet al, 2014).…”
Section: Paracetamol For the Early Management Of Covid-19: A Criticalmentioning
confidence: 99%